Perception of freedom in leisure among substance users and nonusers - Diego Eugênio Roquette Godoy Almeida (Psico-USF, 2018)
The aim of this study was to verify that substance use among adolescents would be linked to perceptions of freedom in leisure. It was selected for convenience sampling 186 adolescents at Projeto Quixote in a public school in Guarulhos. It used as questionnaire Data Sociodemographic and Leisure, The Leisure Diagnostic Battery, version B (PLL) to measure Perceived Freedom in Leisure and Drug Use Screening Inventory for classification of substance use, all self-administered. Based on 165 reviews analyzed, the frequency of use of ecstasy and marijuana in the last month were related to higher rates of PLL. The number of substances used in the last month had no significant effect. These data suggest specific components of leisure related to the frequency of substance use, such as perceived control and need at leisure.